Property theory legal and political perspectives - Penner, J. E. ca. 20./21. Jh; Otsuka, Michael 1964- (Cambridge University Press, 2018)
Property, or property rights, remains one of the most central elements in moral, legal, and political thought. It figures centrally in the work of figures as various as Grotius, Locke, Hume, Smith, Hegel and Kant. This collection of essays brings fresh perspective on property theory, from both legal and political theoretical perspectives, and is essential reading for anyone interested in the nature of property. Edited by two of the world's leading theorists of property, James Penner and Michael Otsuka, this volume brings together essays which consider, amongst other topics, property and public law, the importance of legal forms in property theory, whether use or exclusion are most essential to our understanding of property, distributive justice, Lockean and Grotian theories, the common ownership of the Earth, and Confucian ideas of property